Evaluation of root canal morphology of maxillary second premolars in a Saudi Arabian sub-population: An in vitro microcomputed tomography study - Mutasim Elnour; Abdul Khabeer; Emad AlShwaimi (Saudi Dental Journal)
Aim: To investigate the root canal morphology of maxillary second premolars in a Saudi Arabian subpopulation using microcomputed tomography (micro-CT). Methodology: Micro-CT analysis was performed on 100 maxillary second premolars. The anatomy of each tooth (number of roots, canals, orifices, and apical foramina, and the presence of apical deltas and accessory canals) was analyzed from reconstructed three-dimensional images. Results: The most common morphology was a single root (67%), followed by two roots (30%), and three roots (3%). Regarding the canal morphology, most teeth (65%) contained two canals, followed by 30% with one canal, and 5% with three canals. One orifice was observed in 55% of teeth, and two orifices were detected in 45% of teeth. According to the Vertucci classification, the most common canal types were IV and V (both found in 23% of teeth), followed by type I (17%), type III (9%), type II (7%), and type VII (2%). Additional types that were inconsistent with the Vertucci classification were recorded in 19% of teeth. Conclusion: The root canal morphology of maxillary second premolars in the Saudi Arabian subpopulation is complex and requires cautious evaluation prior to endodontic treatment. Keywords: Maxillary second premolars, Microcomputed tomographic imaging, Root canal morphology